Proper Monitoring and Parenting of the Girl Child in Nigerian Stand-up Comedy - Idowu James Adekunle (Editura Universităţii Aurel Vlaicu Arad, 2021)
Stand-up comedy is an oral dramatic performance that is commonly enacted by a solo-performer or a duet before a live audience. Some existing literatures examined it largely from humour and entertainment to the neglect of its deeper societal values. Therefore, this paper investigates its new trend in gender discourse through its oral structural form by discussing the social responsibility of mothers on proper monitoring and parenting of the girl child. Besides, it also investigates the linguistic devices employed by the selected female comedian to reveal the roles of female comedians as the gatekeepers and conscience of society. Five digital video discs of live performance recordings of Helen Paul, a Nigerian female comedian, were purposively selected. The selected live recordings were based on the informing sociological realities and choice of satiric mode. The paper employed Schechner’s Performance, Freudian and Jungian psychoanalytic theories were used to analyse the informing sociological realities and choice of satiric mode. The data were subjected to performance and literary analysis